Reflexões sobre a vivência no "cantinho do notebook" em uma turma de educação infantil - Machado, Fabiana Regina (2009)
The objective of this study was to verify if the introduction, through the teacher, of the "notebook corner" would change the context of a kindergarten classroom, looking for the changes in children's relationships. The research was supported by a socio-historical theoretical frame based on authors like Vigotski, Luria, Leontiev, Tomasello, Wertsch, Bruner and authors who gave continuity to this approach with the activity theory like Nardi, Kaptelinin, Bodker and Cole. The methodological approach was qualitative research, more specifically action research, conducted inside a classroom from a private school in Curitiba. The participants of this study were four and five year's children with previously computational knowledge belonging to a privileged social class. The methodology was action-research where the researcher was also the teacher of the classroom. The data was collected in two stages. It begins with the application of a questionnaire (pre-artifact) and participant observations (pre and post-artifact). The main results of the study showed that there was significant changes in children's relations due to the information technology as a new language to deal with and, as a result, it promoted the growth of communication and collaboration among children and the real necessity of rules allowing participants to effectively use their autonomy.